Toward an Oral History of Metro Manila’s Railways - Flaviano, Emerald O. (Kasarinlan: Philippine Journal of Third World Studies; Vol 30, No 2-Vol 31, No 1 (2015-2016): Indigenous People and Contested Access to Land, 2017)
This research note outlines the contribution of oral history in the interdisciplinary study “The Mass Transit System in Metro Manila: From Tranvia to MRT, 1879–2014.” It engages the scholarship in oral history to lay down the theoretical bases for the assumptions made in the deployment of oral history—the conduct of the interviews, the method of recording, the analysis of the gathered data—to answer the study’s key research questions. Aside from offering a more nuanced account of the development of urban mass transit, the oral history project will be opening to the public access to the video recordings and transcripts of the interviews—reflecting as well recent discussions about the directions of oral history beyond the interview as method of engagement to issues of storage and access. This accessible online archive is envisioned to be a rich collection of data gathered by the study, which will include not only oral history video recordings and transcripts, but also materials provided by the other component projects of the study.
Keywords: oral history, mass transit, recorded interview, access to oral history